Saberes e práticas de docentes no uso das Tecnologias da Informação e Comunicação (TIC) no ensino superior na saúde - Albuquerque, Antonia Adriana Alves de (2014)
This research describes knowledge and practices of teachers in using ICT in higher education in health. The aim of this study was to know the use of ICT by teachers in the teaching-learning process of a private institution of higher education (Campus I) in the city of Maceió Alagoas. The methodology used was descriptive, cross-sectional, quantitative and qualitative, with the participation of 25 teachers of nursing, pharmacy, physiotherapy, nutrition and dentistry, using a questionnaire with 16 questions, six closed for the characterization of teachers and ten open on ICT in teaching practice. We conclude that the majority of teachers surveyed have teacher training to use ICT and the ICT they use most often were: blog and other social networks, chat, date show, e-mail, discussion forum, video conferencing and wikis. For these teachers, these technologies are important for pedagogical practices, and are now part of daily life for themselves, assisting, promoting and contributing to the teaching-learning process.